The incidence and outcomes of antepartum haemorrhage of unknown origin at Tygerberg Hospital: a retrospective, descriptive study - Hartell, Claudine (Stellenbosch : Stellenbosch University, 2017)
Thesis (MMed)--Stellenbosch University, 2017.